A de novo interstitial deletion of 7q31.2q31.31 identified in a girl with developmental delay and hearing loss. Issue 2 (13th April 2016) - Zhao, Jianhua; Noon, Sarah E.; Krantz, Ian D.; Wu, Yaning
Abstract : We report on a 4‐year‐old female who presented with unilateral sensorineural hearing loss and a concern for developmental delay. A genome‐wide SNP array analysis was performed and revealed a de novo 3.2 Mb interstitial deletion of chromosome 7q31.2q31.31. This region contains thirteen protein‐encoding genes. It is unknown whether haploinsufficiency of any of these genes is responsible for the clinical features of our patient. We reviewed, the clinical phenotype of a previously published 7q31.3 deletion patient and 18 additional patients with overlapping 7q31 deletions listed in the DECIPHER database. The most consistent feature in these patients and our proband is delayed speech and language development. Hearing loss is presented both in our proband and the published 7q31.3 patient. Our study suggests that a small region on chromosome 7q31.3 encompassing four genes, CFTR, CTTNBP2, NAA38, and ANKRD7, may represent a new locus for congenital hearing loss and/or speech development. © 2016 Wiley Periodicals, Inc.